Association of viral RNAs in the choroid plexus with bipolar disorder and schizophrenia and evidence for the hepatitis C virus involvement in neuropathology - Maree J. Webster; Ashwin Balagopal; Jeffrey Quinn; Ou Chen; Sarven Sabunciyan (Translational Psychiatry)
Abstract Many epidemiological studies have shown an association between infectious agents, particularly viruses, and psychiatric disorders including schizophrenia. However, evidence of a viral infection in the brain that associates with schizophrenia (SCZ), bipolar disorder (BPD), and major depression (MDD) has not been found. A potential reason for this discrepancy may be that viruses are more likely to infect the neuroepithelium than neural tissue. To test this hypothesis, we used viral sequence enrichment technology and performed RNA sequencing in postmortem choroid plexus (CP) isolated from 84 SCZ, 73 BPD, 23 MDD cases and 76 unaffected controls (CNT) from the Stanley Medical Research Institute brain collection. This approach enabled us to identify the presence of 13 viral species in the CP of 46 subjects. We discovered that CP samples collected from subjects with SCZ and BPD are more likely to contain viral sequences. In terms of individual viruses, the Hepatitis C Virus (HCV) was the only viral species that reached the threshold of statistical significance for an association with SCZ and BPD. Therefore, we focused on HCV to characterize the association between psychiatric disorders and viruses. Analysis of the TriNetX electronic health record database with data on 285 million patients revealed that the prevalence of chronic HCV was 3.6 and 3.9 percent in the SCZ and BPD populations respectively. The prevalence of chronic HCV in these populations was almost double that observed for MDD (1.8%) and approximately 7-fold higher than the control population (0.5%). These findings confirm previous studies that report higher HCV prevalence in SCZ and BPD and suggest that HCV infection may be associated with disease pathology rather than behaviors such as intravenous drug injection, since these behaviors are present in all three disorders. We analyzed hippocampus RNA sequencing data from the subjects identified to be HCV positive via sequence capture. We found that although the virus was absent in this tissue, HCV RNA in the CP was associated with consistent host transcriptional changes in the hippocampus that were potentially related to the innate immune response. Our results are consistent with previous studies and provide clues regarding the contribution of viruses to the pathology of psychiatric disorders.